Interfacial film for ion battery, preparation method of interfacial film, ion battery and electric device

By performing multi-step modification on carbon nanotubes, an interfacial film with high ionic conductivity and mechanical strength is formed, which solves the battery short circuit problem caused by lithium dendrite growth and improves the cycle stability and electrochemical performance of lithium metal batteries.

CN120682508APending Publication Date: 2025-09-23CNBM ZHEJIANG MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510826861.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-19
Publication Date
2025-09-23

Smart Images

  • Figure BDA0005458306740000171
    Figure BDA0005458306740000171
Patent Text Reader

Abstract

The invention discloses an interfacial film for an ion battery, a preparation method of the interfacial film, the ion battery and an electric device, the interfacial film for the ion battery is finally obtained by performing multi-step modification on a carbon nano tube and reacting the carbon nano tube with a prepolymer solution, so that the interfacial film can effectively reduce the interfacial impedance and promote ion transmission, and the performance of the ion battery is improved. The modified carbon nanotubes are combined with polyimide through the action of covalent bonds, so that the mechanical property of an interfacial film is improved, dendritic crystal puncture can be physically inhibited through the high mechanical strength of the interfacial film, and the cycling stability and the rate capability of the battery are improved; and meanwhile, the interfacial film can inhibit side reaction between the negative electrode and electrolyte, reduce interface impedance and promote ion transmission, so that the overall electrochemical performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to an interface membrane for an ion battery, a preparation method thereof, and an ion battery and an electrical device. Background Art

[0002] Energy has always been a paramount concern for sustainable development in human society. In recent decades, rapid industrialization and increasing energy demand have led to increasing global attention regarding environmental pollution and energy crises. Consequently, countries around the world have been developing new energy sources or using clean, renewable energy to replace traditional fossil fuels. With the growing demand for portable electronics and electric vehicles, the development of secondary batteries with high energy density is urgent. Lithium metal, with its extremely high theoretical specific capacity (3860 mAh / g) and low electrochemical potential (-3.04 V), is considered one of the most promising anode materials. However, due to its relatively high chemical and electrochemical activity, lithium metal readily reacts with liquid electrolytes, forming an unstable solid electrolyte interface (SEI). Non-uniform lithium ion conduction occurs within this interface, leading to the formation of lithium dendrites and "dead lithium." The continued growth of lithium dendrites can penetrate the separator, causing a short circuit in the battery, resulting in high current discharge, significant heat generation, and even fire and explosion.

[0003] The SEI film naturally formed between the metallic lithium negative electrode and the electrolyte should have the function of stabilizing the metallic lithium negative electrode. However, it is often not able to achieve the desired effect due to the influence of various factors such as the degree of reaction and volume effect. Therefore, many scientific researchers are committed to pre-constructing a layer of artificial SEI film on the surface of metallic lithium and precisely controlling its functionality to guide the uniform deposition of lithium ions, inhibit dendrite growth, alleviate the occurrence of interfacial side reactions, and improve the coulombic efficiency of the battery. Compared with inorganic compounds, the toughness and structural designability of polymers give them unique advantages. Their flexibility makes them have a strong ability to adapt to the deformation of the lithium surface and avoid the fracture of the in-situ SEI film during the deposition / stripping process. Polymers have good flexibility and their chemical structure can be designed to provide specific functions.

[0004] Chinese patent application CN110289448A discloses a lithium metal anode with an artificially constructed SEI film. The SEI film constructed by this method is strong and elastic, and can move with the fluctuations of the lithium metal surface during charge and discharge, minimizing the "interfacial distance" and thus preventing the formation of lithium dendrites. However, this invention only utilizes physical properties (the strength and elasticity of the SEI film) to suppress lithium dendrites. As the battery cycles, this SEI film will quickly break down, allowing lithium dendrites to continue to grow.

[0005] Therefore, it is necessary to develop an SEI membrane with good chemical and mechanical stability, electronic insulation but high ionic conductivity, and the ability to regulate lithium dendrite growth. Summary of the Invention

[0006] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide an interface membrane for ion batteries, a preparation method, and an ion battery and electrical device thereof. On the one hand, the interface membrane can effectively limit the direct contact between the electrolyte and the electrode, preventing further decomposition of the electrolyte and destruction of the solid electrolyte interface of the electrode. On the other hand, it also has high ionic conductivity and electronic insulation, stable performance, high cycle number, and good application prospects.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing an interface film for an ion battery comprises the following steps:

[0009] S1. Pretreatment of carbon nanotubes: adding carbon nanotubes to a mixed acid solution for immersion treatment, followed by filtering and washing to obtain acidified carbon nanotubes, then adding the acidified carbon nanotubes to a nickel chloride solution and stirring, filtering and drying after the treatment, and calcining under a hydrogen atmosphere to obtain pretreated carbon nanotubes;

[0010] S2. Preparation of composite carbon nanotubes: Add deionized water to the pretreated carbon nanotubes prepared in step S1, followed by boric acid, melamine, and polyvinyl pyrrolidone, and stir to react. After the reaction is complete, filter, wash, dry, and calcine under a nitrogen atmosphere to obtain composite carbon nanotubes.

[0011] S3. Preparation of modified carbon nanotubes: Add the composite carbon nanotubes prepared in step S2 to an ethanol aqueous solution, followed by aminopropyltriethoxysilane, and heat to react. After the reaction is complete, filter and dry to obtain a solid product. Add 4-ethylenesulfonylbenzoic acid to the EDC / NHS solution, stir for 20-30 minutes, then add the solid product and continue to react at a constant temperature. After the reaction is complete, filter, wash, and dry to obtain modified carbon nanotubes.

[0012] S4. Preparation of polyimide prepolymer: 4,4'-diaminodiphenyl ether and 5-fluoro-2-mercaptobenzoic acid were added to DMF and stirred evenly under nitrogen protection. Then, pyromellitic dianhydride and pyridine were added and reacted for a period of time to obtain a prepolymer solution.

[0013] S5. Preparation of interface film: adding the modified carbon nanotubes in step S3 to the prepolymer solution and dispersing them evenly, then adding benzophenone and reacting under ultraviolet light. After the reaction is completed, the mixed solution is cast into a film, dried, and then imidized. After cooling, the film is peeled off and soaked in ethanol to remove the residual solvent to obtain an interface film.

[0014] Preferably, in step S1, the mixed acid solution is formed by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, the immersion treatment temperature is 30-40°C, and the time is 4-5 hours; the concentration of the nickel chloride solution is 0.1-0.2 mol / L, the stirring treatment temperature is 20-30°C, and the time is 30-40 minutes; the calcination temperature is 450-550°C, and the time is 1.5-2.5 hours.

[0015] In the present invention, by acid-treating carbon nanotubes, oxygen-containing functional groups can be introduced on the surface of carbon nanotubes to improve the dispersion of carbon nanotubes and prevent their agglomeration; at the same time, they also serve as active sites for subsequent chemical modification; the acidified carbon nanotubes are then immersed in a nickel chloride solution, and nickel ions (Ni 2+ ) will be adsorbed onto the oxygen-containing functional groups and defect sites on the surface of the carbon nanotubes, increasing the nickel ion adsorption rate. Finally, it is calcined in a hydrogen atmosphere to form metallic nickel nanoparticles on the surface of the carbon nanotubes, which serve as a catalyst for the subsequent generation of boron nitride, promoting the uniform loading of more boron nitride on the surface of the carbon nanotubes.

[0016] Preferably, in step S2, the mass ratio of the pretreated carbon nanotubes, deionized water, boric acid, melamine, and polyvinyl pyrrolidone is 20-30:800-900:15-20:10-15:1-1.5, the stirring reaction temperature is 80-90°C, the time is 5-6h, and the calcination temperature is 800-1000°C, and the time is 2-3h.

[0017] In the present invention, boron nitride is generated in situ on carbon nanotubes. Boron nitride has excellent ionic conductivity and insulation properties. The loading of a large amount of boron nitride significantly improves the ionic conductivity of the composite carbon nanotubes while maintaining its good electronic insulation, which is crucial for reducing the resistance of the interface film and promoting ion transport.

[0018] Preferably, in step S3, the mass ratio of the composite carbon nanotubes and aminopropyltriethoxysilane is 20-30:3-4, the temperature of the heating reaction is 50-60°C, and the time is 1-2h; the mass ratio of the 4-ethylenesulfonylbenzoic acid and the solid product is 3.5-4.5:20-30, the temperature of the constant temperature reaction is 60-70°C, and the time is 3-4h.

[0019] In the present invention, the composite carbon nanotubes are doubly modified by aminopropyltriethoxysilane and 4-ethylenesulfonylbenzoic acid. On the one hand, siloxane groups are introduced to improve the compatibility of carbon nanotubes with the polymer matrix; on the other hand, the coordination effect of sulfonic acid groups and lithium ions is introduced to reduce the ion diffusion barrier and further improve the ionic conductivity.

[0020] Preferably, in step S4, the mass ratio of the 4,4'-diaminodiphenyl ether, 5-fluoro-2-mercaptobenzoic acid, pyromellitic dianhydride, pyridine, and DMF is 20-30:1.7-2.6:21-32:1.2-1.8:240-300, the reaction temperature is 50-60°C, and the reaction time is 3-4h.

[0021] In the present invention, 5-fluoro-2-mercaptobenzoic acid is added during the preparation of a polyimide prepolymer. These raw materials can undergo a condensation reaction to generate a polyamic acid (PAA) prepolymer solution, thereby introducing fluorine groups and mercapto groups into the polyimide. The fluorocarbon groups can not only enhance the electrolyte corrosion resistance of the interface film, but also enhance the adsorption of ions and reduce the electronic conductivity of the interface film. The mercapto groups can subsequently react with the double bonds on the modified carbon nanotubes to enhance the bonding force between the carbon nanotubes and the polyimide, thereby improving the mechanical properties of the interface film.

[0022] Preferably, in step S5, the mass ratio of the modified carbon nanotubes, prepolymer solution, and benzophenone is 3-5:200-250:0.4-0.8, and the intensity of the ultraviolet light reaction is 10-20 mW / cm 2 , the reaction time is 40-50min; the imidization process is: heating to 80-90℃, keeping warm for 1-1.5h, then heating to 160-180℃, keeping warm for 1-1.5h, and finally heating to 250-300℃, keeping warm for 1-1.5h.

[0023] In the present invention, by reacting modified carbon nanotubes with a prepolymer solution, a stronger chemical bond is formed between the modified carbon nanotubes and the polymer matrix, thereby improving the mechanical strength and stability of the interface film; then, through a gradient imidization process, the prepolymer can be fully reacted to form a stable polyimide structure. This polyimide structure has excellent thermal stability, chemical stability and mechanical strength, and can ensure that the interface film maintains structural integrity during the battery charging and discharging process, thereby extending the battery life.

[0024] The present invention also protects an interface membrane for an ion battery prepared by the method described above.

[0025] Preferably, the thickness of the interface film is 50-200μm, which can be 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, or 200μm. The interface film of the above thickness can effectively separate the negative electrode from the electrolyte in the ion battery to avoid contact between the negative electrode and the electrolyte, and has better mechanical strength, which is beneficial to inhibiting the growth of dendrites in the ion battery.

[0026] The present invention also protects an ion battery, comprising: a negative electrode and a positive electrode arranged opposite to each other; the interface film as described above, wherein the interface film is arranged on the side of the negative electrode close to the positive electrode; and a self-generated interface film, wherein the self-generated interface film is arranged on the surface of the negative electrode close to the interface film, and the self-generated interface film comprises an inorganic salt and an organic salt.

[0027] In the present invention, the negative electrode sheet can be prepared by mixing hard carbon, a conductive agent, and a binder in a specific ratio (e.g., 8:1:1), adding a solvent, grinding the mixture thoroughly, and then coating the mixture on copper foil. The mixture is then dried in an oven. After drying, the mixture is cut into small pieces and stored in a glove box for later use.

[0028] In the present invention, the preparation method of the positive electrode sheet may include: mixing an active material (lithium cobalt oxide, ternary positive electrode, etc.) with a conductive agent and a binder in a certain ratio (e.g., 8:1:1), grinding the mixture thoroughly in an agate mortar, adding a solvent, grinding the mixture into a slurry, applying the slurry to a carbon-coated aluminum foil using a spatula, and then drying the mixture in an oven. After drying, the mixture is cut into small pieces and placed in a glove box for later use.

[0029] In the present invention, the conductive agent used in the method for preparing the positive electrode and the negative electrode is one of acetylene black, conductive carbon black, conductive graphite, carbon nanotubes, graphene, etc.; the binder used in the above method for preparing the positive electrode and the negative electrode is one of sodium carboxymethyl cellulose, sodium alginate, and polyvinylidene fluoride. When preparing the negative electrode, the binder may preferably be sodium carboxymethyl cellulose, and when preparing the positive electrode, the binder may preferably be polyvinylidene fluoride; the solvent used when preparing the negative electrode may be water, and the solvent when preparing the positive electrode may be NMP.

[0030] In the present invention, in the method for manufacturing the positive electrode and the negative electrode, the drying temperature is 60-120° C. and the drying time is 1-20 hours.

[0031] Preferably, the ion battery is a sodium ion battery or a lithium ion battery.

[0032] The present invention also protects an electrical device comprising the ion battery as described above.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The interface membrane for ion batteries provided by the present invention is obtained by multi-step modification of carbon nanotubes and reacting them with a prepolymer solution, and finally obtaining an interface membrane with a specific structure. The boron nitride and sulfonic acid groups contained in the modified carbon nanotubes act together, so that the interface membrane can effectively reduce the interface impedance, promote ion transport, and inhibit side reactions, thereby improving the overall performance of the ion battery. Polyimide helps to maintain the stability of the artificial SEI membrane and inhibits the formation of cracks during lithium deposition / dissolution. The modified carbon nanotubes and polyimide are combined through the action of covalent bonds, thereby improving the mechanical properties of the interface membrane. Its high mechanical strength can physically inhibit dendrite puncture, improve the cycle stability and rate performance of the battery, and at the same time, the interface membrane can inhibit the side reactions between the negative electrode and the electrolyte, reduce the interface impedance,

[0035] Facilitates ion transport, thereby improving the overall electrochemical performance of the battery.

[0036] (2) The interface membrane for ion batteries provided by the present invention improves the dispersibility of carbon nanotubes by acidifying carbon nanotubes, which also serves as an active site for subsequent chemical modification; the acidified carbon nanotubes are then immersed in a nickel chloride solution for immersion treatment, and then calcined in a hydrogen atmosphere to form metal nickel nanoparticles on the surface of the carbon nanotubes, which serve as a catalyst for the subsequent generation of boron nitride, thereby promoting the uniform loading of more boron nitride on the surface of the carbon nanotubes; then boron nitride is in situ generated on the carbon nanotubes, and boron nitride has excellent ionic conductivity and insulation. The loading of a large amount of boron nitride significantly improves the ionic conductivity of the composite carbon nanotubes while maintaining their good electronic insulation, which is crucial for reducing the resistance of the interface membrane and promoting ion transport; then aminopropyltriethoxysilane and 4- The composite carbon nanotubes are doubly modified with ethylene sulfonylbenzoic acid. On the one hand, siloxane groups are introduced to improve the compatibility of the carbon nanotubes with the polymer matrix; on the other hand, the coordination effect of the sulfonic acid groups with lithium ions is introduced to reduce the ion diffusion barrier and further improve the ionic conductivity; at the same time, 5-fluoro-2-mercaptobenzoic acid is added during the preparation of the polyimide prepolymer. These raw materials can undergo a condensation reaction to generate a polyamic acid (PAA) prepolymer solution, thereby introducing fluorine and mercapto groups into the polyimide. The fluorocarbon group can not only enhance the corrosion resistance of the interface film to the electrolyte, but also enhance the adsorption of ions and reduce the electronic conductivity of the interface film; the mercapto group can subsequently react with the double bonds on the modified carbon nanotubes to enhance the bonding force between the carbon nanotubes and the polyimide, thereby improving the mechanical properties of the interface film.

[0037] (3) The interface membrane for ion batteries provided by the present invention can synergize with the self-generated interface membrane (comprising inorganic salts and organic salts) on the surface of the negative electrode to construct a stable double-layer interface structure. This double-layer interface structure can not only effectively prevent the electrolyte from corroding the negative electrode, but also promote the rapid transmission of ions at the interface, thereby significantly improving the cycle stability and rate performance of the ion battery. DETAILED DESCRIPTION

[0038] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0039] The carbon nanotubes have a length of 0.5-2 μm and a diameter of 30-50 nm.

[0040] Example 1

[0041] A method for preparing an interface film for an ion battery comprises the following steps:

[0042] S1. Pretreatment of carbon nanotubes: adding carbon nanotubes to a mixed acid solution (concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) and immersing at 35°C for 4.5 hours, followed by filtering and washing to obtain acidified carbon nanotubes. Subsequently, 50 g of the acidified carbon nanotubes were added to 1 L of nickel chloride solution (concentration of 0.15 mol / L) and treated at 25°C and a stirring speed of 70 r / min for 35 minutes. After the treatment, the mixture was filtered and dried, and calcined at 500°C in a hydrogen atmosphere for 2 hours to obtain pretreated carbon nanotubes.

[0043] S2. Preparation of composite carbon nanotubes: 25 g of the pretreated carbon nanotubes prepared in step S1 were added to 850 g of deionized water, followed by the addition of 18 g of boric acid, 12 g of melamine, and 1.3 g of polyvinyl pyrrolidone. The mixture was reacted at 85° C. and a stirring speed of 120 r / min for 5.5 h. After the reaction was completed, the mixture was filtered, washed, and dried, and calcined at 900° C. for 2.5 h in a nitrogen atmosphere to obtain composite carbon nanotubes.

[0044] S3. Preparation of modified carbon nanotubes: 25 g of the composite carbon nanotubes prepared in step S2 were added to 650 mL of an ethanol-water solution (the volume ratio of ethanol to water was 3:1), followed by the addition of 3.5 g of aminopropyltriethoxysilane, and the mixture was reacted at 55° C. for 1.5 h. After completion of the reaction, the mixture was filtered and dried to obtain a solid product. 4 g of 4-ethylenesulfonylbenzoic acid was added to 650 mL of an EDC / NHS solution (the concentration of EDC was 2.5 g / L and the concentration of NHS was 3.5 g / L), stirred for 25 min, and then 25 g of the solid product was added. The mixture was reacted at a constant temperature of 65° C. for 3.5 h. After completion of the reaction, the mixture was filtered, washed, and dried to obtain modified carbon nanotubes.

[0045] S4. Preparation of prepolymer: 25 g of 4,4'-diaminodiphenyl ether and 2.1 g of 5-fluoro-2-mercaptobenzoic acid were added to 230 g of DMF and stirred evenly under nitrogen protection. Then, 26 g of pyromellitic dianhydride and 1.5 g of pyridine were added and reacted at 55° C. for 3.5 h to obtain a prepolymer solution;

[0046] S5. Preparation of interface film: 4 g of modified carbon nanotubes in step S3 were added to 270 g of prepolymer solution and dispersed evenly. Then, 0.6 g of benzophenone was added and the mixture was reacted under ultraviolet light with an intensity of 15 mW / cm 2 The reaction temperature is 75℃, the reaction time is 45min, and after the reaction is completed, the mixed solution is cast into a film, dried at a pressure of 15kpa and a temperature of 85℃ for 1.5h, and then imidized. The imidization process is: heating to 85℃, keeping warm for 1.5h, then heating to 170℃, keeping warm for 1h, and finally heating to 270℃, keeping warm for 1.5h. After cooling, the film is peeled off, soaked in ethanol for 7, and then vacuum dried at 65℃ for 7.5h to remove the residual solvent to obtain an interface film with a thickness of 80μm.

[0047] Example 2

[0048] A method for preparing an interface film for an ion battery comprises the following steps:

[0049] S1. Pretreatment of carbon nanotubes: adding carbon nanotubes to a mixed acid solution (concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1), immersing at 30°C for 5 hours, then filtering and washing to obtain acidified carbon nanotubes, then adding 50g of the acidified carbon nanotubes to 1L of nickel chloride solution (concentration of 0.1mol / L), treating at 20°C and stirring at 60r / min for 40 minutes, filtering and drying after the treatment, and calcining in a hydrogen atmosphere at 450°C for 2.5 hours to obtain pretreated carbon nanotubes;

[0050] S2. Preparation of composite carbon nanotubes: 20 g of the pretreated carbon nanotubes prepared in step S1 were added to 800 g of deionized water, followed by the addition of 15 g of boric acid, 10 g of melamine, and 1 g of polyvinylpyrrolidone. The mixture was reacted at 80° C. and a stirring speed of 100 r / min for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried, and calcined at 800° C. for 3 h in a nitrogen atmosphere to obtain composite carbon nanotubes.

[0051] S3. Preparation of modified carbon nanotubes: 20 g of the composite carbon nanotubes prepared in step S2 were added to 600 mL of ethanol-water solution (the volume ratio of ethanol to water was 3:1), followed by the addition of 3 g of aminopropyltriethoxysilane, and the mixture was reacted at 50° C. for 2 h. After completion of the reaction, the mixture was filtered and dried to obtain a solid product. 3.5 g of 4-ethylenesulfonylbenzoic acid was added to 600 mL of EDC / NHS solution (the concentration of EDC was 2 g / L and the concentration of NHS was 3 g / L), stirred for 20 min, and then 20 g of the solid product was added. The mixture was reacted at a constant temperature of 60° C. for 4 h. After completion of the reaction, the mixture was filtered, washed, and dried to obtain modified carbon nanotubes.

[0052] S4. Preparation of prepolymer: 20 g of 4,4'-diaminodiphenyl ether and 1.7 g of 5-fluoro-2-mercaptobenzoic acid were added to 200 g of DMF, and stirred evenly under nitrogen protection. Then, 21 g of pyromellitic dianhydride and 1.2 g of pyridine were added, and the mixture was reacted at 50° C. for 4 h to obtain a prepolymer solution;

[0053] S5. Preparation of interface film: 3 g of modified carbon nanotubes in step S3 were added to 240 g of prepolymer solution and dispersed evenly. Then 0.4 g of benzophenone was added and reacted under ultraviolet light with an intensity of 10 mW / cm 2 The reaction temperature is 70℃, the reaction time is 50min, and after the reaction is completed, the mixed solution is cast into a film, dried at a pressure of 20kPa and a temperature of 80℃ for 2h, and then imidization is carried out. The imidization process is: heating to 80℃, keeping warm for 1h, then heating to 160℃, keeping warm for 1.5h, and finally heating to 250℃, keeping warm for 1.5h. After cooling, the film is peeled off, soaked in ethanol for 6h, and then vacuum dried at 60℃ for 8h to remove the residual solvent to obtain an interface film with a thickness of 80μm.

[0054] Example 3

[0055] A method for preparing an interface film for an ion battery comprises the following steps:

[0056] S1. Pretreatment of carbon nanotubes: adding carbon nanotubes to a mixed acid solution (concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1), immersing at 40°C for 4 hours, then filtering and washing to obtain acidified carbon nanotubes, then adding 50g of the acidified carbon nanotubes to 1L of nickel chloride solution (concentration of 0.2mol / L), treating at 30°C and stirring at 80r / min for 30 minutes, filtering and drying after the treatment, and calcining in a hydrogen atmosphere at 550°C for 1.5 hours to obtain pretreated carbon nanotubes;

[0057] S2. Preparation of composite carbon nanotubes: 30 g of the pretreated carbon nanotubes prepared in step S1 were added to 900 g of deionized water, followed by the addition of 20 g of boric acid, 15 g of melamine, and 1.5 g of polyvinyl pyrrolidone. The mixture was reacted at 90° C. and a stirring speed of 130 r / min for 5 h. After the reaction was completed, the mixture was filtered, washed, and dried, and calcined at 1000° C. for 2 h in a nitrogen atmosphere to obtain composite carbon nanotubes.

[0058] S3. Preparation of modified carbon nanotubes: 30 g of the composite carbon nanotubes prepared in step S2 were added to 700 mL of ethanol-water solution (volume ratio of ethanol to water: 3:1), followed by the addition of 4 g of aminopropyltriethoxysilane, and the mixture was reacted at 60° C. for 1 h. After completion of the reaction, the mixture was filtered and dried to obtain a solid product. 4.5 g of 4-ethylenesulfonylbenzoic acid was added to 700 mL of EDC / NHS solution (EDC concentration: 3 g / L, NHS concentration: 4 g / L), stirred for 20 min, and then 0 g of the solid product was added. The mixture was reacted at a constant temperature of 70° C. for 3 h. After completion of the reaction, the mixture was filtered, washed, and dried to obtain modified carbon nanotubes.

[0059] S4. Preparation of prepolymer: 30 g of 4,4'-diaminodiphenyl ether and 2.6 g of 5-fluoro-2-mercaptobenzoic acid were added to 250 g of DMF and stirred evenly under nitrogen protection. Then, 32 g of pyromellitic dianhydride and 1.8 g of pyridine were added and reacted at 60° C. for 3 h to obtain a prepolymer solution;

[0060] S5. Preparation of interface film: 5 g of modified carbon nanotubes in step S3 were added to 300 g of prepolymer solution and dispersed evenly. Then, 0.8 g of benzophenone was added and the mixture was reacted under ultraviolet light with an intensity of 20 mW / cm 2 The reaction temperature is 80℃, the reaction time is 40min, and after the reaction is completed, the mixed solution is cast into a film, dried at a pressure of 10kPa and a temperature of 90℃ for 1h, and then imidization is carried out. The imidization process is: heating to 90℃, keeping warm for 1.5h, then heating to 180℃, keeping warm for 1h, and finally heating to 300℃, keeping warm for 1h. After cooling, the film is peeled off, soaked in ethanol for 8h, and then vacuum dried at 70℃ for 7h to remove the residual solvent to obtain an interface film with a thickness of 80μm.

[0061] Comparative Example 1

[0062] A method for preparing an interface film for an ion battery comprises the following steps:

[0063] S1. Preparation of composite carbon nanotubes: 25 g of pretreated carbon nanotubes were added to 850 g of deionized water, followed by 18 g of boric acid, 12 g of melamine, and 1.3 g of polyvinyl pyrrolidone. The mixture was reacted at 85° C. and a stirring speed of 120 r / min for 5.5 h. After the reaction was completed, the mixture was filtered, washed, and dried, and calcined at 900° C. for 2.5 h in a nitrogen atmosphere to obtain composite carbon nanotubes.

[0064] S2. Preparation of modified carbon nanotubes: 25 g of the composite carbon nanotubes prepared in step S1 were added to 650 mL of an ethanol-water solution (the volume ratio of ethanol to water was 3:1), followed by the addition of 3.5 g of aminopropyltriethoxysilane, and the mixture was reacted at 55° C. for 1.5 h. After completion of the reaction, the mixture was filtered and dried to obtain a solid product. 4 g of 4-ethylenesulfonylbenzoic acid was added to 650 mL of an EDC / NHS solution (the concentration of EDC was 2.5 g / L and the concentration of NHS was 3.5 g / L), stirred for 25 min, and then 25 g of the solid product was added. The mixture was reacted at a constant temperature of 65° C. for 3.5 h. After completion of the reaction, the mixture was filtered, washed, and dried to obtain modified carbon nanotubes.

[0065] S3. Preparation of prepolymer: 25 g of 4,4'-diaminodiphenyl ether and 2.1 g of 5-fluoro-2-mercaptobenzoic acid were added to 230 g of DMF and stirred evenly under nitrogen protection. Then, 26 g of pyromellitic dianhydride and 1.5 g of pyridine were added and reacted at 55° C. for 3.5 h to obtain a prepolymer solution;

[0066] S4. Preparation of interface film: 4 g of modified carbon nanotubes prepared in step S2 were added to 270 g of prepolymer solution and dispersed evenly. 0.6 g of benzophenone was then added and reacted under ultraviolet light with an intensity of 15 mW / cm 2 The reaction temperature is 75℃, the reaction time is 45min, and after the reaction is completed, the mixed solution is cast into a film, dried at a pressure of 15kpa and a temperature of 85℃ for 1.5h, and then imidized. The imidization process is: heating to 85℃, keeping warm for 1.5h, then heating to 170℃, keeping warm for 1h, and finally heating to 270℃, keeping warm for 1.5h. After cooling, the film is peeled off, soaked in ethanol for 7, and then vacuum dried at 65℃ for 7.5h to remove the residual solvent to obtain an interface film with a thickness of 80μm.

[0067] Compared with Example 1, the carbon nanotubes were not pretreated in this comparative example.

[0068] Comparative Example 2

[0069] A method for preparing an interface film for an ion battery comprises the following steps:

[0070] S1. Pretreatment of carbon nanotubes: adding carbon nanotubes to a mixed acid solution (concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) and immersing at 35°C for 4.5 hours, followed by filtering and washing to obtain acidified carbon nanotubes. Subsequently, 50 g of the acidified carbon nanotubes were added to 1 L of nickel chloride solution (concentration of 0.15 mol / L) and treated at 25°C and a stirring speed of 70 r / min for 35 minutes. After the treatment, the mixture was filtered and dried, and calcined at 500°C in a hydrogen atmosphere for 2 hours to obtain pretreated carbon nanotubes.

[0071] S2. Preparation of modified carbon nanotubes: 25 g of the pretreated carbon nanotubes in step S1 were added to 650 mL of ethanol aqueous solution (the volume ratio of ethanol to water was 3:1), followed by the addition of 3.5 g of aminopropyltriethoxysilane, and the mixture was reacted at 55° C. for 1.5 h. After completion of the reaction, the mixture was filtered and dried to obtain a solid product; 4 g of 4-ethylenesulfonylbenzoic acid was added to 650 mL of EDC / NHS solution (the concentration of EDC was 2.5 g / L and the concentration of NHS was 3.5 g / L), stirred for 25 min, and then 25 g of the solid product was added. The mixture was reacted at a constant temperature of 65° C. for 3.5 h. After completion of the reaction, the mixture was filtered, washed, and dried to obtain modified carbon nanotubes;

[0072] S3. Preparation of prepolymer: 25 g of 4,4'-diaminodiphenyl ether and 2.1 g of 5-fluoro-2-mercaptobenzoic acid were added to 230 g of DMF and stirred evenly under nitrogen protection. Then, 26 g of pyromellitic dianhydride and 1.5 g of pyridine were added and reacted at 55° C. for 3.5 h to obtain a prepolymer solution;

[0073] S4. Preparation of interface film: 4 g of modified carbon nanotubes prepared in step S2 were added to 270 g of prepolymer solution and dispersed evenly. 0.6 g of benzophenone was then added and reacted under ultraviolet light with an intensity of 15 mW / cm 2 The reaction temperature is 75℃, the reaction time is 45min, and after the reaction is completed, the mixed solution is cast into a film, dried at a pressure of 15kpa and a temperature of 85℃ for 1.5h, and then imidized. The imidization process is: heating to 85℃, keeping warm for 1.5h, then heating to 170℃, keeping warm for 1h, and finally heating to 270℃, keeping warm for 1.5h. After cooling, the film is peeled off, soaked in ethanol for 7, and then vacuum dried at 65℃ for 7.5h to remove the residual solvent to obtain an interface film with a thickness of 80μm.

[0074] Compared with Example 1, in this comparative example, boron nitride is not loaded on the carbon nanotubes.

[0075] Comparative Example 3

[0076] A method for preparing an interface film for an ion battery comprises the following steps:

[0077] S1. Pretreatment of carbon nanotubes: adding carbon nanotubes to a mixed acid solution (concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) and immersing at 35°C for 4.5 hours, followed by filtering and washing to obtain acidified carbon nanotubes. Subsequently, 50 g of the acidified carbon nanotubes were added to 1 L of nickel chloride solution (concentration of 0.15 mol / L) and treated at 25°C and a stirring speed of 70 r / min for 35 minutes. After the treatment, the mixture was filtered and dried, and calcined at 500°C in a hydrogen atmosphere for 2 hours to obtain pretreated carbon nanotubes.

[0078] S2. Preparation of composite carbon nanotubes: 25 g of the pretreated carbon nanotubes prepared in step S1 were added to 850 g of deionized water, followed by the addition of 18 g of boric acid, 12 g of melamine, and 1.3 g of polyvinyl pyrrolidone. The mixture was reacted at 85° C. and a stirring speed of 120 r / min for 5.5 h. After the reaction was completed, the mixture was filtered, washed, and dried, and calcined at 900° C. for 2.5 h in a nitrogen atmosphere to obtain composite carbon nanotubes.

[0079] S3. Preparation of modified carbon nanotubes: 25 g of the composite carbon nanotubes prepared in step S2 were added to 650 mL of an ethanol-water solution (the volume ratio of ethanol to water was 3:1), followed by the addition of 3.5 g of aminopropyltriethoxysilane. The mixture was reacted at 55° C. for 1.5 h. After the reaction was complete, the mixture was filtered and dried to obtain modified carbon nanotubes.

[0080] S4. Preparation of prepolymer: 25 g of 4,4'-diaminodiphenyl ether and 2.1 g of 5-fluoro-2-mercaptobenzoic acid were added to 230 g of DMF and stirred evenly under nitrogen protection. Then, 26 g of pyromellitic dianhydride and 1.5 g of pyridine were added and reacted at 55° C. for 3.5 h to obtain a prepolymer solution;

[0081] S5. Preparation of interface film: 4 g of modified carbon nanotubes in step S3 were added to 270 g of prepolymer solution and dispersed evenly. Then, 0.6 g of benzophenone was added and the mixture was reacted under ultraviolet light with an intensity of 15 mW / cm 2 The reaction temperature is 75℃, the reaction time is 45min, and after the reaction is completed, the mixed solution is cast into a film, dried at a pressure of 15kpa and a temperature of 85℃ for 1.5h, and then imidized. The imidization process is: heating to 85℃, keeping warm for 1.5h, then heating to 170℃, keeping warm for 1h, and finally heating to 270℃, keeping warm for 1.5h. After cooling, the film is peeled off, soaked in ethanol for 7, and then vacuum dried at 65℃ for 7.5h to remove the residual solvent to obtain an interface film with a thickness of 80μm.

[0082] Compared with Example 1, in this comparative example, 4-ethylenesulfonylbenzoic acid was not introduced onto the carbon nanotubes.

[0083] Comparative Example 4

[0084] A method for preparing an interface film for an ion battery comprises the following steps:

[0085] S1. Pretreatment of carbon nanotubes: adding carbon nanotubes to a mixed acid solution (concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1) and immersing at 35°C for 4.5 hours, followed by filtering and washing to obtain acidified carbon nanotubes. Subsequently, 50 g of the acidified carbon nanotubes were added to 1 L of nickel chloride solution (concentration of 0.15 mol / L) and treated at 25°C and a stirring speed of 70 r / min for 35 minutes. After the treatment, the mixture was filtered and dried, and calcined at 500°C in a hydrogen atmosphere for 2 hours to obtain pretreated carbon nanotubes.

[0086] S2. Preparation of composite carbon nanotubes: 25 g of the pretreated carbon nanotubes prepared in step S1 were added to 850 g of deionized water, followed by the addition of 18 g of boric acid, 12 g of melamine, and 1.3 g of polyvinyl pyrrolidone. The mixture was reacted at 85° C. and a stirring speed of 120 r / min for 5.5 h. After the reaction was completed, the mixture was filtered, washed, and dried, and calcined at 900° C. for 2.5 h in a nitrogen atmosphere to obtain composite carbon nanotubes.

[0087] S3. Preparation of modified carbon nanotubes: 25 g of the composite carbon nanotubes prepared in step S2 were added to 650 mL of an ethanol-water solution (the volume ratio of ethanol to water was 3:1), followed by the addition of 3.5 g of aminopropyltriethoxysilane, and the mixture was reacted at 55° C. for 1.5 h. After completion of the reaction, the mixture was filtered and dried to obtain a solid product. 4 g of 4-ethylenesulfonylbenzoic acid was added to 650 mL of an EDC / NHS solution (the concentration of EDC was 2.5 g / L and the concentration of NHS was 3.5 g / L), stirred for 25 min, and then 25 g of the solid product was added. The mixture was reacted at a constant temperature of 65° C. for 3.5 h. After completion of the reaction, the mixture was filtered, washed, and dried to obtain modified carbon nanotubes.

[0088] S4. Preparation of prepolymer: 25 g of 4,4'-diaminodiphenyl ether was added to 230 g of DMF and stirred evenly under nitrogen protection. Then, 26 g of pyromellitic dianhydride and 1.5 g of pyridine were added and reacted at 55° C. for 3.5 h to obtain a prepolymer solution;

[0089] S5. Preparation of interface film: 4 g of modified carbon nanotubes in step S3 were added to 270 g of prepolymer solution and dispersed evenly. Then, 0.6 g of benzophenone was added and the mixture was reacted under ultraviolet light with an intensity of 15 mW / cm 2The reaction temperature is 75℃, the reaction time is 45min, and after the reaction is completed, the mixed solution is cast into a film, dried at a pressure of 15kpa and a temperature of 85℃ for 1.5h, and then imidized. The imidization process is: heating to 85℃, keeping warm for 1.5h, then heating to 170℃, keeping warm for 1h, and finally heating to 270℃, keeping warm for 1.5h. After cooling, the film is peeled off, soaked in ethanol for 7, and then vacuum dried at 65℃ for 7.5h to remove the residual solvent to obtain an interface film with a thickness of 80μm.

[0090] Compared with Example 1, this comparative example does not introduce 5-fluoro-2-mercaptobenzoic acid into the polyimide. The interface films prepared in Examples 1-3 and Comparative Examples 1-4 were applied to button-type lithium-ion batteries to test their electrical properties. The button-type lithium-ion batteries were prepared by mixing hard carbon, a binder (polyvinylidene fluoride), and a conductive agent (carbon black SP) in a mass ratio of 8:1:1, and applying the resulting mixture to copper foil at a coating density of 10 mg / cm 2 Then it is dried at 100℃ and rolled to a compaction density of 1.5g / cm 3 , cut into discs as negative electrode sheets; lithium iron phosphate is mixed with a conductive agent (carbon black SP) and a binder (polyvinylidene fluoride) in a mass ratio of 8:1:1, fully ground in an agate mortar, and solvent NMP is added. After grinding into a slurry, it is coated on a carbon-coated aluminum foil with a spatula and then placed in an oven for drying at 80°C for 10 hours. After drying, it is cut into small pieces and placed in a glove box for standby use; a 13 μm thick PE material is selected as a diaphragm (porosity of about 48%); the electrolyte consists of a solvent, an additive and a lithium salt LiPF6, the solvent is ethylene carbonate (EC) and propylene carbonate in a mass ratio of 1:1, the additive is fluoroacetate (FEC) accounting for 5% of the solvent mass, and the concentration of LiPF6 in the electrolyte is 1.0 mol·L -1 The total amount of electrolyte added was 0.1 mL, and the negative electrode, interface film, electrolyte, separator, and positive electrode were assembled into a button cell in a glove box. The results are shown in Table 1.

[0091] Table 1

[0092]

[0093] As can be seen from Table 1 above, the interface film prepared by the present invention has high ionic conductivity and electronic insulation, stable performance, high cycle number, and good application prospects.

[0094] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an interface membrane for an ion battery, characterized in that: The following steps are involved: S1, adding carbon nanotubes to a mixed acid solution for immersion treatment to obtain acidified carbon nanotubes, then adding them to a nickel chloride solution for stirring treatment, filtering, drying, and calcining to obtain pretreated carbon nanotubes; S2, adding the pretreated carbon nanotubes to deionized water, followed by adding boric acid, melamine, and polyvinyl pyrrolidone, stirring to react, filtering, washing, drying, and calcining to obtain composite carbon nanotubes; S3, adding the composite carbon nanotubes to an ethanol aqueous solution, followed by adding aminopropyltriethoxysilane, heating for reaction, filtering, and drying to obtain a solid product; adding 4-ethylenesulfonylbenzoic acid to the EDC / NHS solution, followed by adding the solid product, and reacting at a constant temperature to obtain modified carbon nanotubes; S4, adding 4,4'-diaminodiphenyl ether and 5-fluoro-2-mercaptobenzoic acid to DMF, followed by adding pyromellitic dianhydride and pyridine, and reacting to obtain a prepolymer solution; S5. Adding the modified carbon nanotubes to the prepolymer solution, followed by adding benzophenone, and performing ultraviolet light reaction. Then, the mixed solution is cast into a film, and after drying, imidization is performed to obtain an interface film.

2. The preparation method according to claim 1, characterized in that In step S1, the mixed acid solution is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:

1. The immersion treatment temperature is 30-40°C and the time is 4-5 hours. The concentration of the nickel chloride solution is 0.1-0.2 mol / L. The stirring treatment temperature is 20-30°C and the time is 30-40 minutes. The calcination temperature is 450-550°C and the time is 1.5-2.5 hours.

3. The preparation method according to claim 1, characterized in that In step S2, the mass ratio of the pretreated carbon nanotubes, deionized water, boric acid, melamine, and polyvinyl pyrrolidone is 20-30:800-900:15-20:10-15:1-1.5, the stirring reaction temperature is 80-90°C, the time is 5-6h, and the calcination temperature is 800-1000°C, and the time is 2-3h.

4. The preparation method according to claim 1, characterized in that In step S3, the mass ratio of the composite carbon nanotubes and aminopropyltriethoxysilane is 20-30:3-4, the temperature of the heating reaction is 50-60°C, and the time is 1-2 hours; the mass ratio of the 4-ethylenesulfonylbenzoic acid and the solid product is 3.5-4.5:20-30, the temperature of the constant temperature reaction is 60-70°C, and the time is 3-4 hours.

5. The preparation method according to claim 1, characterized in that In step S4, the mass ratio of 4,4'-diaminodiphenyl ether, 5-fluoro-2-mercaptobenzoic acid, pyromellitic dianhydride, pyridine, and DMF is 20-30:1.7-2.6:21-32:1.2-1.8:200-250, the reaction temperature is 50-60°C, and the reaction time is 3-4h.

6. The preparation method according to claim 1, characterized in that In step S5, the mass ratio of the modified carbon nanotubes, prepolymer solution, and benzophenone is 3-5:240-300:0.4-0.8, and the intensity of the ultraviolet light reaction is 10-20 mW / cm 2 , the reaction temperature is 70-80°C, and the reaction time is 40-50min; the imidization process is: heating to 80-90°C, keeping warm for 1-1.5h, then heating to 160-180°C, keeping warm for 1-1.5h, and finally heating to 250-300°C, keeping warm for 1-1.5h.

7. An interface membrane for an ion battery prepared by the method according to any one of claims 1 to 6.

8. An ion battery, characterized in that: include: A negative electrode and a positive electrode arranged opposite to each other; the interface film as described in claim 7, wherein the interface film is arranged on the side of the negative electrode close to the positive electrode; a self-generated interface film, wherein the self-generated interface film is arranged on the surface of the negative electrode close to the interface film, and the self-generated interface film includes inorganic salts and organic salts.

9. The ion battery according to claim 8, characterized in that The ion battery is a sodium ion battery or a lithium ion battery.

10. An electrical device, characterized in that: The electrical device comprises the ion battery according to claim 8 or 9.

Citation Information

Patent Citations

  • Metal lithium negative electrode with artificially constructed SEI film and preparation method thereof

    CN110289448A

Cited By

  • Lithium-rich manganese-based positive electrode material and preparation method thereof

    CN122177811A

  • A lithium-rich manganese-based positive electrode material and a preparation method thereof

    CN122177811B